Exploring UUM student’s intention towards participation in service learning for academic purpose based on Technology Acceptance Model (TAM) - Mohd Zahid, Siti Zahirah; Abdul Jabbar, Hijattulah; Romle, Abd Rahim; Mat Isa, Nurul Hasanah; Che Embi, Mariatul Shima (INSInet Publications, 2015)
Service learning that features mutually constructed community are based on service that can enhance the understanding of a range of concepts.Service-learning practitioners were formulated the community engagement activities to make our students in powerful and even transformative ways.Thus, Technology Acceptance Model (TAM) is employed to explore on students’ perception towards their participation in service learning, and that higher perceived usefulness, along with higher perceived ease of subject, leads to more favorable attitudes toward the service learning and stronger intentions for use in future.The primary goal of this paper is to propose a theoretical framework into how service-learning impacts the development and transition of pathway for the students